2019
DOI: 10.1002/oby.22623
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Weight Loss After Sleeve Gastrectomy and Adjustable Gastric Banding: Far More Than Just Restriction

Abstract: Obesity has reached global epidemic proportions in recent decades. Bariatric surgery is currently accepted as most effective in alleviating morbid obesity and related disorders. Sleeve gastrectomy (SG) and adjustable gastric banding (AGB) have gained popularity since the beginning of this century because of their efficacy, safety, and simplicity. SG, in particular, has emerged as the most popular bariatric procedure because of its simpler concept and shorter operative time compared with gastric bypass. Caloric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 99 publications
0
15
0
1
Order By: Relevance
“…Although it may be counterintuitive that a smaller gastric reservoir does not improve weight loss, this approach is mechanistically supported: weight loss from sleeve gastrectomy has more to do with complex physiologic (eg, gastric emptying time) and neurohormonal factors (eg, eliminating ghrelin secretion from the gastric fundus) than with simple volume restriction. [22][23][24] The decreased capacitance of narrower sleeves may thus increase reflux risk without improving weight loss. In addition, the operations studied were performed after a specialty-wide shift toward more consistent bougie sizing, between 34F and 36F, potentially leading the analysis to underestimate the potential association of bougie size with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although it may be counterintuitive that a smaller gastric reservoir does not improve weight loss, this approach is mechanistically supported: weight loss from sleeve gastrectomy has more to do with complex physiologic (eg, gastric emptying time) and neurohormonal factors (eg, eliminating ghrelin secretion from the gastric fundus) than with simple volume restriction. [22][23][24] The decreased capacitance of narrower sleeves may thus increase reflux risk without improving weight loss. In addition, the operations studied were performed after a specialty-wide shift toward more consistent bougie sizing, between 34F and 36F, potentially leading the analysis to underestimate the potential association of bougie size with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The greater fat mass losses observed following RYGB relative to gastric banding might be related to the greater increases in glucagon‐like peptide‐1 (GLP‐1) that occur following RYGB compared with gastric banding 43 . GLP‐1 is known to increase post‐prandial insulin secretion and induce a sensation of satiety, thus making it a key factor for the regulation of glucose and appetite control 44 . This is supported by the 1‐year post‐surgery outcomes of Holter et al, 45 which demonstrated that patients affected by obesity and T2DM who undergo RYGB have a higher insulin secretion rate within the first 60 min and lower glucose levels 120 min after ingesting glucose, compared with those who undergo gastric banding.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to determine whether these changes in hormone levels are in fact causal to weight loss. Studies regarding other factors that contribute to bariatric surgeries ( Madsbad et al, 2014 ; Wang et al, 2019 ) such as vagal and hypothalamic activity, role of bile acids, and gut flora alterations are lacking. More studies are encouraged to elucidate the detailed mechanisms of weight and energy regulation and glucose metabolism after use of gastric bariatric devices.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that additional factors beyond restriction exist. It seems that gastric motility, neural activity, ghrelin level, concentrations of gut hormones, energy expenditure, bile acids metabolism, and gut microbial diversity play important roles; however, the conclusions varied significantly ( Wang et al, 2019 ). For example, Aron-Wisnewsky et al (2019) observed that gut microbial gene abundance increased after AGB whereas Lee et al (2019) reported an opposite result.…”
Section: Introductionmentioning
confidence: 99%